Effectiveness of Geogebra Integration into Flipped Classroom (GFC) on Students Mathematics Skills: A Meta-Analysis Study - Cahyani, Izza Alfina; Sujarwo, Sujarwo; Imaroh, Yunianti Risma; Hukom, Julham; Yanuar, Fahd Sjarifain; Martaputri, Nurul Aulia; Nisrina, Nisrina (FKIP Universitas Lampung, 2024)
Effectiveness of Geogebra Integration into Flipped Classroom (GFC)on Students Mathematics Skills: A Meta-Analysis Study. Previous research examining the effectiveness of Geogebra Integration into Flipped Classroom (GFC) on students' mathematics skills showed inconsistent results. Objectives: This research aims to conduct a meta-analysis study on the effectiveness of Geogebra integration into Flipped Classroom (GFC) and identify what factors moderate the effect of GFC on students' mathematical skills. Methods: The research method used meta-analysis. The samples in this study were 31 primary studies that met the specified inclusion criteria. Data analysis was conducted using comprehensive meta-analysis (CMA) software. Findings: The results of the analysis using the random-effects approach showed that the combined effect size was (g = 1.06; p < 0.01) (Large Effect Category). This indicates that GFC has a significant influence on students' mathematics skills. The result of moderator variable analysis shows that the effect of GFC implementation on students' mathematics skills is significantly different based on the variable of platform used (Qb = 21.98; p = 0.01), and publication type (Qb = 7.94; p = 0.01). However, it was not significantly different based on the variables of education level (Qb = 7.45; p = 0.06), experimental group capacity (Qb = 0.29; p = 0.62), and year of publication (Qb = 0.21; p = 0.64). The findings of this meta-analysis can serve as a basis for best practices in applying GFC to student mathematics skills Conclusion: The findings of this meta-analysis provide more accurate and comprehensive results regarding the inconsistent effects of size variation and enrich knowledge about the effectiveness of using GFC in improving students' mathematics skills. Keywords: geogebra into flipped classroom, mathematics skill, meta-analysis.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024119